Knowledge and practice regarding Kala-azar among community people of Dangihat, Morang - Bista, Sita; Sapkota, Sochana; Akela, Govinda (Journal of Chitwan Medical College, 2017)
Out of 12 endemic districts of Nepal still 11 districts have been reported with Kala-azar, among which Morang is the one. It is useful to identify knowledge and practice of people regarding disease for its effective management. But there is dearth of the related study in our country. So this study aimed to assess the knowledge and practice regarding Kala-azar among community people of Dangihat, Morang. A descriptive cross-sectional study was carried out among community people of Dangihat-4, Morang within age group 15-60 years. Interview of 91 respondents by using semi structured questionnaires schedule with purposive convenience sampling technique was done from 3rd Ashwin to 24th Ashwin, 2072. The study showed that only 18.7% had correct knowledge of sandfly while majority (63.7%) thought mosquito as the vector of disease. Regarding symptoms 94.5% and 73.6% mentioned fever and blackening of skin respectively. Two third of the respondents thought cattle shed as the habitat of sandfly and 67% mentioned its biting time to be dusk/ dawn. Most (89%) of the respondents used bed nets and 44% used insecticide for prevention of Kala-azar. There was significant association between knowledge with previous history and source of information of disease and practice with educational level. Most (52.7%) of the respondents had inadequate knowledge while 78% had average practice regarding Kala-azar. The study population had inadequate knowledge and average practice of disease so further awareness programme may be needed in the village.